(untitled) (Czech Journal of International Relations, 2000)
The author of this essay informs the reader of the results of the fourth phase of the grant project of the Ministry of Foreign Affairs of the Czech Republic, directed at research of the attitudes of the population of our state towards Germany in 1999. This phase concentrated on several major aspects of Czech-German relations, especially the frequency of contacts between the citizens of the two states, Germany’s influence on the accession of the Czech Republic to the European Union, the way citizens assess the role of the Czech-German Declaration, the manner in which the Sudeten German question is being reflected and the evaluation of Germany as a significant political, economic and cultural partner/neighbour of the Czech Republic. The aim of this project has been to give the authors of Czech foreign policy a complete picture of the way Czech society reflects relations with its most significant neighbouring country, especially in the light of the specific aspect of bilateral relations, namely the Sudeten German question. At the same time, the historical burden on mutual relations remains an emotive potential, capable of mobilizing Czech society in the event that fundamental foreign policy decisions are at variance with views and attitudes shared by sections of society. A comparison of the latest phase with the results of earlier research projects, carried out since 1996, offers a number of most interesting findings on the current form of the so-called historical memory which contains, among other things, the factor of the historical burden on Czech-German relations, while at the same time capturing the dynamics of the emergence of new relations towards the Federal Republic of Germany as our ally in the North Atlantic Alliance and as to a geographically closest partner in the European Union whose position will to a considerable extent influence the decision on the membership of the Czech Republic in this major association of European states.